A novel variant of DNM1L expanding the clinical phenotypic spectrum: a case report and literature review - Zhenkun Zhang; Xiaofan Bie; Zhehui Chen; Jing Liu; Zhenhua Xie; Xian Li; Mengjun Xiao; Qiang Zhang; Yaodong Zhang; Yanling Yang; Dongxiao Li (BMC, 2024)
Abstract Background Mitochondrial diseases are heterogeneous in terms of clinical manifestations and genetic characteristics. The dynamin 1-like gene (DNM1L) encodes dynamin-related protein 1 (DRP1), a member of the GTPases dynamin superfamily responsible for mitochondrial and peroxisomal fission. DNM1L variants can lead to mitochondrial fission dysfunction. Case presentation Herein, we report a distinctive clinical phenotype associated with a novel variant of DNM1L and review the relevant literature. A 5-year-old girl presented with paroxysmal hemiplegia, astigmatism, and strabismus. Levocarnitine and coenzyme Q10 supplement showed good efficacy. Based on the patient's clinical data, trio whole-exome sequencing (trio-WES) and mtDNA sequencing were performed to identify the potential causative genes, and Sanger sequencing was used to validate the specific variation in the proband and her family members. The results showed a novel de novo heterozygous nonsense variant in exon 20 of the DNM1L gene, c.2161C>T, p.Gln721Ter, which is predicted to be a pathogenic variant according to the ACMG guidelines. The proband has a previously undescribed clinical manifestation, namely hemiparesis, which may be an additional feature of the growing phenotypic spectrum of DNM1L-related diseases. Conclusion Our findings elucidate a novel variant in DNM1L-related disease and reveal an expanding phenotypic spectrum associated with DNM1L variants. This report highlights the necessity of next generation sequencing for early diagnosis of patients, and that further clinical phenotypic and genotypic analysis may help to improve the understanding of DNM1L-related diseases.